Corporate Governance Characteristics and Company Performance - Saragih, Ferdinand Dehoutman; Nugroho, Bernardus Yuliarto; Eko, Umanto (UI Scholars Hub, 2013)
The research analyzes the determinant of corporate governance characteristic in relation to company performance in family firms listed in Indonesia Stock Exchange in the period of 2004-2009. The research uses quantitative approach, explanatory type and uses numerical data as secondary data obtained from various sources. The result shows that only PER variable is significantly influenced by corporate governance characteristic with proxies of ownerships, board size, and board composition, and controlled with the variables of sales, firm age, firm leverage, tangibility, firm size, growth, and debt in public firms listed in Indonesia Stock Exchange in the period of 2004-2009; in general, investors basically perceive company performance from the market value ratio in the form of company’s stock price interchange instead of the profitability ratio with the proxies of ROA and ROE; the variables of ownerships, board size, and board composition statistically do not affect ROA, ROE, and PER.